Les guides européens et leurs auteurs : clefs de lecture - Goulven Guilcher (In Situ)
After explaining how a collection of guides is built up in connection with research at university level this article studies the genesis of the main three european collections of guidebooks in the XIXth century: Murray, Baedeker and Joanne-Hachette. By means of a detailed comparative analysis GoulvenGuilcher describes the features that characterize them. He also deals with the room left by these collections for other types of guides and the influence exerted by the authors of the guides and the heads of collections over the contents of these publications. By close scrutiny the specialist is able to determine in what way guidebooks take into account the uses of tourism, at the same time by means of advice to travellers and through advertisements. The bibliophile assesses maps and illustrations offeredin the guides in order to give an image of the countries they describe.